Factors Related to Workplace Violence Towards Nurses in University Hospitals, The People’s Republic of China - Yun, Wu Hai; Akkadechanunt, Thitinut; Wichaikhum , Orn-anong (Nursing Journal CMU, 2022)
Workplace violence is a significant phenomenon in healthcare settings. Nurses are one of the main groups at risk from workplace violence. The purposes of this study were to explore workplace violence (WPV) towards nurses, and to examine the association between personal factors, workplace factors and workplace violence towards nurses in university hospitals, the People’s Republic of China. The participants consisted of 297 nurses who worked in two university hospitals in Yunnan, the People’s Republic of China. The research instrument was the Chinese Version of the Workplace Violence in the Health Sector Questionnaire (CWPVQ). The test-retest reliability were between .84 to .90. Data were analyzed using descriptive statistics, Pearson’s chi-square and Fisher’s exact test. The results of this study were as follows: 1. The prevalence of total workplace violence towards nurses in the preceding year was 79.79%; the prevalence of physical and psychological violence was 74.74% and 5.05%, respectively; and the prevalence of verbal abuse was 70.73%. 2. The factors related to the prevalence of workplace violence towards nurses were the availability of measures such as “changed shifts or rotas” and “reduced periods of working alone”. 3. The factors related to physical violence towards nurses were the departments where the nurses worked and the availability of policies regarding health and safety. 4. The factors related to psychological violence towards nurses were age, the availability of measures such as “changed shifts or rotas” and “reduced periods of working alone”. The findings of this research suggest that hospital directors and nurse administrators should be aware of workplace violence and carry out effective interventions, appropriate strategies and programs to prevent and control workplace violence in university hospitals.